DATA ANALYTICS AND ITS METHODS OF DEVELOPMENT (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The article discusses characteristics of data analysis and what role does different types of data analysis play in collecting informations? Data analysis is a technique used by academics to turn data into a narrative and then interpret it to draw conclusions. Different techniques such as modeling to reach trends, relationships, and therefore conclusions to address the decision-making process are employed in this process.